PENGARUH DISIPLIN KERJA GURU TERHADAP DISIPLIN BELAJAR SISWA SEKOLAH DASAR - Iswan, Iswan; Hadidah, Indah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study are 1) knowing the application of the work discipline of teachers in SDN 02 Sawangan Depok, 2) knowing the application of student learning discipline in SDN 02 Sawangan Depok, and 3) knowing the effect of the teacher's work discipline on the learning discipline of fourth grade students in the SDN 02 Sawangan Depok.This research uses a quantitative approach. Data was collected by distributing questionnaires to 30 students as respondents. Test the validity and reliability of the questionnaire in this study using the Statistical Package for the Social Sciences (SPSS) program with type 21.00.The results showed that 1) based on the results of the rating scale analysis test obtained a questionnaire value of 1150 with intervals ranging from 1081-1440. This means that the application of the work discipline of teachers in SDN 02 Sawangan Depok in the category of "Very Good". 2) the application of student learning discipline in class IV at SDN 02 Sawangan Depok based on the results of the scalae rating analysis test obtained a questionnaire value of 1494 the interval ranged from 1441-1920, so it can be concluded student discipline in the SDN 02 Sawangan Depok in the category of "Very Good". 3) there is a significant influence between the teacher's work discipline on student learning discipline at SDN 02 Sawangan Depok which is supported by a correlation number of 0.409> rtable 0.374 at a significance level of 5% and also the results of the F test which show an Fcount of 5.617> Ftable of 4.20. Because the value of the correlation test shows rcount> of rtable and the results of a simple regression test show that Fcount> Ftable it can be stated that the hypothesis there is an influence between the teacher's work discipline variables on student learning discipline is accepted. While seen from the coefficient of determination (R) of 16.7% it is known that the influence between the teacher's work discipline variables on student learning discipline is 16.7% which is quite influential.